Eventos de produção de texto em sala de aula: em busca do primado da palavra outra - Sacoman, Kelly Cristina Bognar (2012)
This work is an investigation about the texts productions written by children of the second year of elementary school in a public school located in the city of Bauru, in order to seek in the process of construction of the sense of the texts the singularities that point to the relation of the word itself with the word another. To this end, we based ourselves on the theory and design of language of Mikhail Bakhtin, as well as on the ponziana and geraldiana theories with respect to the enunciative treaty of language. In this context, we aimed to understand how occurred the literacy process in what circumscribes the practices of texts production and reading, as well as investigate the conceptions of subject that underlie the different practices of reading and writing in literacy. In addition, we conceive the production practice of written text as a discursive activity that correlates sense (implied) and situation (life) in a unique and singular event. We had as goal, also, think about the senses and subject formation processes in the production of language. With basis on the investigative principles of indiciary paradigm and the methodological reflections in Bakhtin Humanities, we try to highlight in a written narrative production, namely, the children's tale Little Red Riding Hood, how the child assumes a active responsive position on its re-telling. In the narrated discourse there are displacement movements that point to a emotive-valuation work, in which stands out the uniqueness of the child; in the meeting between reported word and word that reports, the child's production is characterized as a translation work.